On Uniqueness of General Equilibrium - Iritani, Jun (Review of Economic Studies, 1981)
Journal Article On Uniqueness of General Equilibrium Get access Jun Iritani Jun Iritani Kyota Sangyo University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 48, Issue 1, January 1981, Pages 167–171, https://doi.org/10.2307/2297129 Published: 01 January 1981 Article history Received: 01 September 1979 Accepted: 01 May 1980 Published: 01 January 1981